2020
DOI: 10.1080/22221751.2020.1725399
|View full text |Cite
|
Sign up to set email alerts
|

RNA based mNGS approach identifies a novel human coronavirus from two individual pneumonia cases in 2019 Wuhan outbreak

Abstract: From December 2019, an outbreak of unusual pneumonia was reported in Wuhan with many cases linked to Huanan Seafood Market that sells seafood as well as live exotic animals. We investigated two patients who developed acute respiratory syndromes after independent contact history with this market. The two patients shared common clinical features including fever, cough, and multiple ground-glass opacities in the bilateral lung field with patchy infiltration. Here, we highlight the use of a low-input metagenomic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
495
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 550 publications
(524 citation statements)
references
References 14 publications
5
495
0
9
Order By: Relevance
“…Then the full genome sequence of SARS-CoV-2 (29870-bp, excluding the poly (A) tail) in GenBank (accession number MN908947) was released quickly on January 10, 2020, which is more than 82% identical to those of SARS-CoV and bat SARS-like coronavirus (SL-CoV) 12 . On the basis of analysis of this complete genomes obtained in this study, several laboratories developed molecular detection tools based on targeting ORF1ab, RNA-dependent RNA polymerase (RdRp) gene N, and E regions of viral spike genes [13][14][15] . And then the rapid identification of this novel coronavirus is attributed to recent advances in the detection of SARS-CoV-2, including RT-PCR, real-time reverse transcription PCR (rRT-PCR), reverse transcription loop-mediated isothermal amplification (RT-LAMP), and microarray-based assays.…”
Section: Identification Of Pathogens Mainly Includes Virus Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Then the full genome sequence of SARS-CoV-2 (29870-bp, excluding the poly (A) tail) in GenBank (accession number MN908947) was released quickly on January 10, 2020, which is more than 82% identical to those of SARS-CoV and bat SARS-like coronavirus (SL-CoV) 12 . On the basis of analysis of this complete genomes obtained in this study, several laboratories developed molecular detection tools based on targeting ORF1ab, RNA-dependent RNA polymerase (RdRp) gene N, and E regions of viral spike genes [13][14][15] . And then the rapid identification of this novel coronavirus is attributed to recent advances in the detection of SARS-CoV-2, including RT-PCR, real-time reverse transcription PCR (rRT-PCR), reverse transcription loop-mediated isothermal amplification (RT-LAMP), and microarray-based assays.…”
Section: Identification Of Pathogens Mainly Includes Virus Isolationmentioning
confidence: 99%
“…And the patients confirmed with the COVID-19 pneumonia had 2 or 3 continuous negative RT-PCR results for nasopharyngeal and throat swab specimens can discharge from hospital. However, the scholar around china indicated that cases of COVID-19 that had 2 or 3 continuous negative RT-PCR results for nasopharyngeal and throat swab specimens before finally laboratory-confirmed [13]. And currently, several reports has reported the positive RT-PCR results for stool of COVID-19 patients 16,17 .…”
Section: Identification Of Pathogens Mainly Includes Virus Isolationmentioning
confidence: 99%
“…The causative pathogen of the COVID-19 outbreak has been identified as a highly infectious novel coronavirus which is referred to as the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). [1][2][3] The transmission of SARS-CoV-2 in humans is thought to be via at least 3 sources: 1) inhalation of liquid droplets produced by and/or 2) close contact with infected persons and 3) contact with surfaces contaminated with SARS-CoV-2. 4 Moreover, aerosol transmission of pathogens has been shown in confined spaces.…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 detection from COVID-19 patient samples in Wuhan, China. Samples testing positive(1)(2)(3)(4)(5)(6) or negative(7) with commercial RT-qPCR tests were assayed using colorimetric LAMP assay with primer set targeting ORF1a (A) and GeneN (B). Yellow indicates a positive detection after 30 min incubation, and pink a negative reaction with results compared to the negative control (N).…”
mentioning
confidence: 99%